Regulatory actions of melatonin in rodent Sertoli cells - Rossi, Soledad Paola (2018)
Melatonin acting through the hypothalamus and pituitary regulates testicular function. In addition, direct actions of melatonin at testicular levels have also been detected. Recently, we described a protective role of melatonin against free radical damage in testicular mast cells. The aim of this study was to investigate the participation of melatonin in the regulation of the oxidative state and lactate dehydrogenase (Ldh) expression in Sertoli cells. For this purpose, we used Sertoli cells isolated from 21 days old Syrian hamsters and the murine TM4 Sertoli cell line, both expressing the melatonergic receptor subtype 1.